Hearing Loss and Associated Factors Among Noise-Exposed Workers in Palm Oil Mills - Rasasoran DR; Atil A; Jeffree MS; Saupin S; Lukman KA (Dove Medical Press, 2021)
Daniel Raj Rasasoran,1 Azman Atil,2 Mohammad Saffree Jeffree,2 Sahipudin Saupin,2 Khamisah Awang Lukman3 1Department of Occupational Safety and Health, Kota Kinabalu, Sabah, Malaysia; 2Occupational and Environmental Health Unit, Community and Family Medicine Department, Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, Kota Kinabalu, Malaysia; 3Centre for Occupational Safety and Health, Universiti Malaysia Sabah, Kota Kinabalu, MalaysiaCorrespondence: Mohammad Saffree JeffreeOccupational and Environmental Health Unit, Community and Family Medicine Department, Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, Jalan UMS, Kota Kinabalu, 88400, Sabah, MalaysiaTel +6088-320000 (ext 611001)Fax +6088-321377Email saffree@ums.edu.myIntroduction: Almost 90% of the reported occupational diseases in Sabah, Malaysian Borneo were due to hearing loss. The manufacturing industry was the main contributor to this problem. This study aims to identify the prevalence and associated factors for hearing loss among workers in the palm oil manufacturing industry in Sabah.Material and Methods: A cross-sectional study was done among 312 respondents from five palm oil mills in Sabah from January to April 2019. Audiometric tests, validated questionnaires and sound level meters were used. Chi-square test and independent t-test were conducted to determine the associated factors for hearing loss.Results: 75% (n = 234) of the respondents were diagnosed with hearing loss. Most of them were male (96.2%) with a mean age of 44.4 (SD 9.8) years, mean duration of employment of 16.2 (SD 9.7) years and mean noise exposure of 96.1 (SD 4.8) dB(A). The significant factors associated with hearing loss were older age (p = 0.001), married (p = 0.001), blue-collar jobs (p = 0.003), smoking (p = 0.001), works with noisy machinery (p = 0.005), lower level of noise exposed (p = 0.015), longer duration of employment (p = 0.001), and longer overtime hours per week (p = 0.001).Conclusion: The prevalence of hearing loss among workers in the noise-exposed palm oil industries was high. Annual audiometry testing and job rotation from noise-exposed workstations were recommended. A smoking cessation program may help but reduction of noise from the source by engineering control is still the best method.Keywords: hearing loss, palm oil mill, noise exposed workers